False-Negative Rate of Gram-Stain Microscopy for Diagnosis of Septic Arthritis: Suggestions for Improvement. (13th February 2014) - Stirling, Paul; Faroug, Radwane; Amanat, Suheil; Ahmed, Abdulkhaled; Armstrong, Malcolm; Sharma, Pankaj; Qamruddin, Ahmed
Abstract : We quantify the false-negative diagnostic rate of septic arthritis using Gram-stain microscopy of synovial fluid and compare this to values reported in the peer-reviewed literature. We propose a method of improving the diagnostic value of Gram-stain microscopy using Lithium Heparin containers that prevent synovial fluid coagulation. Retrospective study of the Manchester Royal Infirmary microbiology database of patients undergoing synovial fluid Gram-stain and culture between December 2003 and March 2012 was undertaken. The initial cohort of 1896 synovial fluid analyses for suspected septic arthritis was reduced to 143 after exclusion criteria were applied. Analysis of our Gram-stain microscopy yielded 111 false-negative results from a cohort size of 143 positive synovial fluid cultures, giving a false-negative rate of 78%. We report a false-negative rate of Gram-stain microscopy for septic arthritis of 78%. Clinicians should therefore avoid the investigation until a statistically significant data set confirms its efficacy. The investigation's value could be improved by using Lithium Heparin containers to collect homogenous synovial fluid samples. Ongoing research aims to establish how much this could reduce the false-negative rate.